Antibacterial activity and mechanism of sanguinarine against Staphylococcus aureus by interfering with the permeability of the cell wall and membrane and inducing bacterial ROS production - Gu, Yeqing; Dong, Jun; Li, Jing; Luo, Qianmin; Dong, Xianlan; Tang, Guowen; Zhang, Jiaxiang; Du, Xuan; Pu, Qiqi; He, Lin; Zhao, Kaiwei; Han, Diangang; et al. (Frontiers in Veterinary Science, 2023)
Sanguinarine chloride hydrate (SGCH) is the hydrochloride form of sanguinarine (SG), one of the main extracts of Macleaya cordata (M. cordata). Staphylococcus aureus (SA) is representative of gram-positive bacteria. However, there are few reports on its antibacterial mechanism against SA. In this study, we investigated the in vitro antibacterial activity and antibacterial mechanism of SGCH against SA, measured the inhibitory zone, minimum inhibitory concentrations (MIC) and minimum bactericidal concentrations (MBC), and plotted the bactericidal activity curve. In addition, the micromorphology, alkaline phosphatase (AKP) activity, Na+K+, Ca2+Mg2+-adenosine triphosphate (ATP) activity, intracellular reactive oxygen species (ROS) and fluorescein diacetate (FDA) were observed and detected. The results showed that the inhibitory zone of SGCH against SA was judged as medium-sensitive; the MIC and MBC were 128 and 256 μg/mL, respectively; in the bactericidal activity curve, SGCH with 8 × MIC could completely kill SA within 24 h. SGCH was able to interfere with the integrity and permeability of the SA cell wall and membrane, as confirmed by the scanning electron microscopy (SEM) images, the increase in extracellular AKP and Na+ K+, Ca2+ Mg2+-ATP activities as well as the fluorescein diacetate (FDA) staining experiment results. Moreover, a high concentration of SGCH could induce SA to produce large amounts of ROS. In summary, these findings revealed that SGCH has a preferable antibacterial effect on SA, providing an experimental and theoretical basis for using SG as an antibiotic substitute in animal husbandry and for the clinical control and treatment of diseases caused by SA.